The Phenomenon of Familiarity in the Scientific Heritage of M. M. Bakhtin - Osmukhina, Olga Yurievna (Journal of History Culture and Art Research, 2020)
The paper considers the phenomenon of familiarity in the context of the carnival theory of the outstanding Russian scientist M. M. Bakhtin, whose work influenced the development of humanitarian thought in Russia and the west of the 20th century. The author of the article investigates the formation of this concept and its influence on the formation and development of the novel genre as one of the components of the folk-laughter culture. Familiarity is a free and unofficial communication without any distance or etiquette norms. Free communication allows you to retreat from the hierarchical and official relations between people. At the same time, the familiar areal speech, through which familiar communication is built, has got its own special characteristics. The speech includes curses, oath, false vows, and obscenities. Therefore, this speech is ambivalent, it is isolated and completed. They are the source of such a phenomenon as familiarity. In this case, familiarity as a category has several levels. The semantic level is associated with informality and the rejection of normativity. The verbal level consists of the specific familiar-square forms and genres, and therefore it contributes to the formation of a special unofficial language. These two levels create a collective, in which familiar treatment is possible. This collective becomes a fair, a carnival crowd. In addition, over time, forms of familiarity have become a kind of protest against the official ideological system.